EXPLORING THE IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING IN TEACHING SPEAKING TO SECONDARY EFL LEARNERS: A QUALITATIVE CASE STUDY - Tiaranisa Nurhadi; Sidik Indra Nugraha; Iwan Ridwan (IKIP Siliwangi, 2024)
This study explores the implementation of Task-Based Language Teaching (TBLT) in teaching speaking to secondary English as a Foreign Language (EFL) learners. Recognizing the importance of speaking proficiency in effective communication, this research aims to investigate the methods and strategies employed by a teacher in a secondary EFL classroom in Bekasi, focusing on the benefits experienced by students in learning speaking skills through TBLT. Through qualitative methods, including class observations and interviews, the findings revealed that TBLT enhances classroom effectiveness, boosts student participation, and improves speaking proficiency by engaging learners in real-world communicative tasks. This study contributes to the existing knowledge on language teaching methodologies, offering practical recommendations for improving speaking proficiency through TBLT strategies in secondary EFL learning environments. The results also provide valuable insights for future researchers, educators, and students, highlighting the potential of TBLT in fostering a learner-centered and interactive classroom atmosphere.